Acoustic characterization of crack damage evolution in sandstone deformed under conventional and true triaxial loading. Issue 6 (22nd June 2017) - Browning, J.; Meredith, P. G.; Stuart, C. E.; Healy, D.; Harland, S.; Mitchell, T. M.
Abstract: We present a comparative study of crack damage evolution in dry sandstone under both conventional ( σ 1 > σ 2 = σ 3 ), and true triaxial ( σ 1 > σ 2 > σ 3 ) stress conditions using results from measurements made on cubic samples deformed in three orthogonal directions with independently controlled stress paths. To characterize crack damage, we measured the changes in ultrasonic compressional and shear wave velocities in the three principal directions, together with the bulk acoustic emission (AE) output contemporaneously with stress and strain. We use acoustic wave velocities to model comparative crack densities and orientations. In essence, we create two end‐member crack distributions; one displaying cylindrical transverse isotropy (conventional triaxial) and the other planar transverse isotropy (true triaxial). Under the stress conditions in our experiments we observed an approximately fivefold decrease in the number of AE events between the conventional and true triaxial cases. When taken together, the AE data, the velocities, and the crack density data indicate that the intermediate principal stress suppresses the total number of cracks and restricts their growth to orientations subnormal to the minimum principal stress. However, the size of individual cracks remains essentially constant, controlled by the material grain size. Crack damage is only generated when the differential stress exceeds some threshold value. Cyclic loading experiments show that further damage commences only when that previous maximum differential stress is exceeded, regardless of the mean stress, whether this is achieved by increasing the maximum principal stress or by decreasing the minimum principal stress. Key Points: The onset of crack damage is a function of increasing differential stress, regardless of whether mean stress is increasing or decreasing The intermediate principal stress then controls the amount of crack damage that ensues and preferentially aligns cracks, but mean crack size remains the same Cyclic stressing shows that the transition from elastic to inelastic behavior (damage envelope) is dynamic and evolves with stress level